TRANSPORTASI DAN NAVIGASI WISATA DENGAN KENDALI ROBOTFUZZY - Naili Suri Intizhami; Faisal; Faisal Akib (Prodi Teknik Informatika Universitas Islam Negeri Makassar, 2021)
The automatic transportation robotis one of the mobile robotsdesigned to be able to take visitors around the zoo area. This robot uses the Arduino Nano as a robot control system, uses a DC motor as a wheel drive motor and is also equipped with a proximity sensor (ping) which will read if there are obstacles in front of the robot, because the zoo has the concept of freeing the animals from roaming around, so that when an animal is is on the track, this robot can find out and immediately stop so there is no collision. The research method used is quantitative research. The quantitative research conducted is an experimental research method. By conducting experiments on control variables (input) to analyze the resulting output. The result of this research is an automatic transportation robotwith8photodiodesensorsaslinefollowersbyimplementingfuzzy logicasthecontrolsystem